Mutu Pola Pendidikan Karakter Pluralisme Pada Siswa Sekolah Menengah Atas: The Quality Pattern of Pluralism Character Education in High School Students - Peni, Natalia; Priska, Melani (Universitas Muhammadiyah Sidoarjo, 2019)
The research aim is to observe the profile and description of thecharacter education in senior high school students. study was conducted in six Senior high schools of city consisting of: State Senior high school 1 of ; State Senior high school 2 of ; Muhammadiyah Senior high school of ; Mudmainah Senior high school of ; Catholic Senior high school St. of ; specifically class X of social science, with a sample of 300 students. Data collection methods used were questionnaires and interviews, and then analyzed using qualitative and quantitative descriptive analysis. The results showed that the profile and description of the pluralism character education patterns quality in six senior high schools of city were very good category with intervals value of 80-100 %. The data shows that the quality of pluralism character education patterns is very good, with the pluralism character education pattern applied to senior high school students through exemplary teacher, religious approach, individual, and nationality.